Liberação de Trichogramma pretiosum (Hym.: Trichogrammatidae) e avaliação de Trichogrammatidae em posturas de Spodoptera frugiperda (Lep.: Noctuidae) na cultura do milho - Camera, Cátia (2009)
Fall armyworm, Spodoptera frugiperda (J.E. Smith), is considered the major pest of corn. In general, the control of larvae is achieved with insecticides application, which can cause several environmental problems. In search of alternative control methods, egg parasitoids of the genus Trichogramma have been used in applied biological control programs, since they are aggressive in the host search. Therefore, the objective of this study was to evaluate aspects related with S. frugiperda control efficiency, in field corn, through Trichogramma pretiosum. Experiments were made in two periods: in 2006/2007 at 10º District Arroio Grande, Santa Maria, RS, and in 2007/2008, in two growth seasons, at Pinheirinho, Santa Bárbara do Sul, RS, where three situations were compared: one area was maintained only with S. frugiperda natural control, other with about 110 thousand T. pretiosum release per hectare, and a third with chemical control application, with 150 mL/ha of Rimon® 100 EC (novarulon) and 60 mL/ha Lannate® BR (metomil); each area with 30 x 30 m. The experimental design was randomized blocks with sampling in the plots. Each period and growth season were considered one repetition, therefore comprising three repetitions. All areas were divided in 16 plots, where the evaluations were made. Six plants per plot were sampled randomly and evaluated, and the plants were examined for: the presence or absence of S. frugiperda egg masses, the egg masses location at the plant and on the surface of the leaf, and the presence or absence of damage caused by the fall armyworm. The evaluations were performed daily, reducing the frequency as the presence of egg masses decreased. On each date, the phenological stage of plants was checked and, daily, reported the air temperature and rainfall. At the end of the crop cycle, the yield was assessed. The collected egg masses were taken to the Laboratory of Entomology, Department of Plant Protection, CCR/UFSM, where they were packed in gelatin capsules, and subsequently analyzed for the hatching of larvae or the emergence of parasitoids. The emerged male parasitoids were identified. As main results, it is possible to point out: S. frugiperda preferred to oviposit in the median part of the plant and the abaxial surface of the leaf and, preferentially, in the early stages (V1-V8) of the crop; natural parasitism of S. frugiperda eggs by richogramatids was low; in RS, S. frugiperda eggs can be parasitized by T. pretiosum, Trichogramma atopovirilia, Trichogramma rojasi and Trichogrammatoidea sp., with predominance of the first two (around 70 and 30% of identified parasitoids, respectively); T. rojasi and, possibly, Trichogrammatoidea sp. had the first record of occurrence in S. frugiperda eggs; plants without damages caused by fall armyworm predominate until the V5 stage, and with more severe damage (perforated leaf) from V6 to V10; the chemical control, with metomil (Lannate® BR) and novaluron (Rimon® 100 EC), does not interfere in the number of eggs or egg masses of S. frugiperda as well as in the parasitoids population; and one release of T. pretiosum does not result in increase in the rate of parasitized eggs and the yield of corn crop.